Photovoltaics and the Solar Rebound: Evidence for Germany - Manuel Frondel; Kathrin Kaestner; Stephan Sommer; Colin Vance (ZBW - Leibniz Information Centre for Economics, 2021)
Recent research suggests that households would increase their electricity consumption in the aftermath of installing photovoltaics (PV) panels, a behavioral change commonly referred to as the solar rebound. Drawing on panel data originating from the German Residential Energy Consumption Survey (GRECS), we employ panel estimation methods and the dynamic system estimator developed by Blundell and Bond (1998) to investigate the solar rebound effect, thereby accounting for simultaneity and endogeneity issues relating to PV installation and the electricity price. Our empirical results suggest that PV panel adoption of households hardly reduces the amount of electricity taken from the grid. As we derive theoretically, this outcome implies that the rebound reaches a maximum that is bounded by about 30% for German households. Yet, we are skeptical of whether there is such a large solar rebound effect given the strong economic incentives to feed solar electricity into the public grid in the past
Keywords: C23; H10; Q41; 330; Feed-in tariffs; GMM system estimator; German Residential Energy Consumption Survey (GRECS)